Calculation the Cross Sections of 10B(n,p)10Be Reaction by Using the Reciprocity Theory for the First Excited State - Ebrahiem, S. A.; Mahdi, K. H.; Taki, A. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this study light elements 10B , 10Be for 10B(n,p)10Be reaction as well as proton energy from 0.987 MeV to 2.028 MeV with threshold energy (1.04MeV) are used according to the available data of reaction cross sections. The more recent cross sections data of 10Be(p,n)10B reaction is reproduced in fin steps in the specified energy range , as well as cross section (p,n) values were derived from the published data of (n,p) as a function of energy in the same fine energy steps by using the reciprocity theory of principle inverse reaction . This calculation involves only the first excited state of  10B , 10Be in the reactions 10Be(p,n)10B and  10B(n,p)10Be.